Nemipterid fishes (Spariformes, Nemipteridae) of Tanzania, with description of a new species of Parascolopsis and new records of Nemipterus elaine and Parascolopsis akatamae - Matiku, Patroba; Bogorodsky, Sergey V.; Samucidine, Kelvin E.; Matcher, Gwynneth; Bills, Roger (Zootaxa, 2026)
Eight species of nemipterid fishes (Nemipteridae) in three genera, collected in coastal waters of Tanzania, are reviewed. Six species were collected during an ecosystem survey conducted by the R/V Dr. Fridtjof Nansen off the coast of Tanzania in 2023 (Nemipterus bipunctatus, N. elaine, N. zysron, Parascolopsis flavimarginatus sp. nov., Scolopsis bimaculata, and S. curite) and two species were found in a museum collection (Parascolopsis akatamae and Scolopsis ghanam). Among these, Nemipterus elaine, previously known only from Mozambique, is recorded from Tanzania for the first time; previous records of N. japonicus and N. randalli from the southwestern Indian Ocean can also be attributed to N. elaine. Parascolopsis akatamae is a new record for Tanzania. Parascolopsis flavimarginatus sp. nov., described from a single specimen, is morphologically similar to P. akatamae and P. eriomma in possessing a high number of gill rakers on the first gill arch (16–19 in these three species, vs. 8–14 gill rakers in other congeners), but can be distinguished by scales on top of head extending forward to above the anterior margin of pupil (vs. scales not extending anterior to a line through middle of eye), and the spinous portion of the dorsal fin being translucent with a broad yellow margin (vs. spinous portion entirely salmon pink, a mixture of salmon pink and yellow, or with a broad reddish margin). Parascolopsis flavimarginatus sp. nov. further differs from all other species of the genus in having a more slender body (body depth of 3.6 in SL, vs. 2.4–3.3 in SL in other species). In addition, the new species differs from all congeners except Parascolopsis tosensis in having a lower number of pectoral-fin rays (14 vs. 15–17 in other species). Descriptions of each species are based on voucher specimens and are accompanied by photographs of fresh specimens. Using tissue samples obtained from fresh voucher material, a phylogenetic analysis of the COI gene region was conducted for all eight species collected from Tanzanian waters.